A COMMON FUTURE: THE ROLE OF THE CIRCULAR ECONOMY AND GREEN ENERGY IN CREATING SUSTAINABLE DEVELOPMENT - CHURIKANOVA, Olena; TURCHANINOVA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Circular economy is one of the main strategies for achieving sustainable development and combating environmental problems. This article explores the issue of introducing circular business models in Ukraine, taking into account the problems and challenges faced by companies and the state. One of the main challenges for the introduction of a circular economy is the need to change ideas about the use of resources and waste. Many companies have become accustomed to a linear model of production, where the costs of resources and energy have not been properly evaluated. Therefore, new approaches to the design and production of products are needed that allow reuse of resources and reduction of waste. The article discusses various business models of the circular economy, such as "product-service", "secondary market", "recycling", "exchange", "rental". An algorithm for introducing these business models in Ukraine, taking into account legislation and market conditions, is also provided. The authors of the article draw attention to the need for state support and openness to new initiatives in this area. Effective implementation of the circular economy requires investment in research and development, infrastructure development and legislative change. In summary, this article provides a clear overview of the circular economy and business models that can be used to achieve sustainable development and combat environmental challenges. It also highlights the problems and challenges that arise during the implementation of circular business models in Ukraine and provides an algorithm for their implementation, taking into account legislation and market conditions. The article emphasizes the need for state support and openness to new initiatives in this area. Introducing a circular economy is an important step towards achieving sustainable development and preserving the environment for future generations.